New-onset mental disorders increase among patients with metabolic diseases after the COVID-19 pandemic - Jeong Min Cho; Jae-ik Oh; Jung Hun Koh; Minsang Kim; Seung Geun Kim; Semin Cho; Soojin Lee; Yaerim Kim; Yong Chul Kim; Seung Seok Han; Hajeong Lee; Kwon-Wook Joo; et al. (Scientific Reports)
Abstract There is limited information on new-onset mental disorders in adults with metabolic diseases following the COVID-19 pandemic. Here, we aimed to examine the changes in mental health following the COVID-19 pandemic and identify factors associated with the development of new-onset mental disorders. Among 90,580 UK Biobank participants diagnosed with COVID-19 between Jan 31, 2020 and Oct 31, 2022, those who completed both baseline and follow-up mental health questionnaires in 2016–2017 and 2022–2023 were included in the analysis. New-onset depression, anxiety, and alcohol use disorder following the COVID-19 pandemic, as well as changes in mental health scores, were assessed. Furthermore, their association with sociodemographic, clinical, and self-perceived emotional state-related exposures was examined. Prevalent metabolic diseases were significantly associated with a higher risk of new-onset depression (hypertension: odds ratio [OR], 1.22; 95% CI 1.01–1.47; diabetes: OR 1.8; 95% CI 1.25–2.6; obesity: OR 1.66; 95% CI 1.43–1.95) and anxiety (hypertension: OR 1.32; 95% CI 1.06–1.63; diabetes: OR 1.66; 95% CI 1.06–2.62; obesity: OR 1.2; 95% CI 0.99–1.44) following COVID-19 pandemic. There was a significant increase of Patient Health Questionnaire-9 (PHQ-9; beta, 0.32; 95% CI 0.29–0.35) and Generalized Anxiety Disorder-7 (GAD-7; beta, 0.10; 95% CI 0.06–0.13) scores throughout the COVID-19 pandemic, while Alcohol Use Disorder Identification Test (AUDIT) score decreased over time (beta, − 0.24; 95% CI − 0.30 to − 0.18). Preexisting metabolic diseases were associated with the accelerated increase in the PHQ-9 and GAD-7 scores following the pandemic. Adults with metabolic diseases are associated with an increased risk of new-onset depression, anxiety, and alcohol use disorders following the COVID-19 pandemic.